The Post 1997-Crtsis Democratization In South Korea (a case study of industrial relations - Tit Lus Warsito (FH 2004 UMY, 2015)
The field research was set to find out the correlations between the 1997 monetary crisis and the process ot democralic consolidation in South Korea, especially in term of industrial relations. As complementary components of industnalization; slate, business and labors are, by nalure, often pertormed conflictual actions. Like in many other developing contries or newly industrializing countries, South Korea experienced a shong developmential siate regime where state have a very tight relations with business group, while their labor policy was badly repressive. But as the 1997 crisis occ,llrred, the three conflicting and competing parties seemed to agree to some points according to solve the problems affected by the crisis The process of democratic consolidation seem to be swifted becâ‚¬use of it.